Las nominaciones de Dios en el argumento del Proslogion - José Luis Gaona Carrillo (Medievalista)
Saint Anselm of Canterbury was a Benedictine monk who wrote the Proslogion argument in the 11th century. The nominations or names of God, are the different ways by which Saint Anselm explained the divine attributes. From a reinterpretation of Ricardo O. Díez’s study ¿Si hay Dios, quién es? an identity between the being and the truth of God is proposed, thus implying a mutual relationship between these attributes with the Anselmian definition of truth. The sentence fides quaerens intellectum will represent a methodology or model through which the thought is oriented in the rational clarification of these divine nominations. However, the same intellectual search will recognize a rational limitation against what it believes by faith. The nominations of the Proslogion and the definition of the truth of the De Veritate allow us to think of an identity that relates both works of Anselmian thought, identity that this article wanted to propose.